Red books, green hills : (Center for Natural Resources and Environmental Studies, Hanoi University, 1996)
This study is one component of a larger servey of Vinh Phu province coorganized by CRES, ENV, and UCB. From these three collaborating institutions, three research groups formed to investigate various aspects of environmental and natural resouces management problems in Vinh Phu,...